Southern sudan secession… causes and repercussions - Sallat , Aiman (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The Study deals mainly with the historical Roots of the Southern Sudan Crisis until the Separation by talking about the causes of the Crisis and its aftermath, and the successive Sudanese Governments. It also tackles the way to settle the Crisis from the early 1990s until the Comprehensive Peace Agreement CPA, known as the Naivasha Agreement 2005. The Study also discusses the international Roles in supporting the conflicting Parties on the Ground in order to achieve Separation, and the local and international reactions to it. The Study also discusses the repercussions of the Separation and its Effects on the Sudan, on the Countries of the Region " Nile Valley", and the Region in general.